Microstructure and mechanical property of novel NiAl-based hypoeutectic/eutectic/hypereutectic high-entropy alloy. (April 2022) - Wang, Lei; Su, Yanning; Yao, Chengli; Huang, Yuandong; Shen, Jun; Zhang, Yunpeng; Liu, Gang; Zhao, Pengkang; Zhang, Guojun
Abstract: In this paper, we investigate the microstructures and mechanical properties of novel NiAl-Mo x Cr x V x, NiAl-Mo y Cr y Fe y and NiAl-Mo z Cr z V z Fe z eutectic high-entropy alloy (EHEA) systems. The microstructures of three alloy systems change from hypoeutectic (primary NiAl + eutectic, x  = 7.5, 8.33/ y  = 13.33, 14.0/ z  = 9.0, 9.5, hypo-EHEA) to eutectic ( x  = 8.7/ y  = 14.5/ z  = 10.0, EHEA) and then to hypereutectic (primary MoCrV/MoCrFe/MoCrVFe + eutectic, x  = 9.0, 10.0/ y  = 15.0, 16.0/ z  = 10.5, 11.0, hyper-EHEA). The microhardness of primary MoCrV/MoCrFe/MoCrVFe is higher than that of primary NiAl. It almost has a rule that the yield strength gradually increases from hypo-EHEA to EHEA, and then to hyper-EHEA, which is attributed to a certain amount of high-microhardness primary MoCrV/MoCrFe/MoCrVFe phase in hyper-EHEA. For the EHEAs, the microstructures of NiAl–Mo8.7 Cr8.7 V8.7 /NiAl–Mo14.5 Cr14.5 Fe14.5 /NiAl–Mo10 Cr10 V10 Fe10 are composed of eutectic cells or eutectic dendrites which consist of NiAl (B2) and MoCrV/MoCrFe/MoCrVFe (BCC) lamellar phases, respectively. It is also found that the plenty of fine (Ni, Al)-rich precipitates occur in MoCrFe and MoCrVFe phases (SEM images). Moreover, according to the phase composition, it is determined that MoCrV/MoCrFe/MoCrVFe is a high entropy phase, thus possessing a better strengthening effect on NiAl. Correspondingly, three EHEAs possess the good mechanical properties, and the microhardness and the yield strength exhibit an increased trend: NiAl–Mo8.7 Cr8.7 V8.7  < NiAl–Mo14.5 Cr14.5 Fe14.5  < NiAl–Mo10 Cr10 V10 Fe10 EHEAs. The major strengthening mechanisms are the solution strengthening and the precipitation strengthening. Highlights: Three NiAl-based hypo-EHEA, EHEA and hyper-EHEA systems are carefully investigated. NiAl–Mo8.7 Cr8.7 V8.7 /NiAl–Mo14.5 Cr14.5 Fe14.5 /NiAl–Mo10 Cr10 V10 Fe10 has eutectic composition. Eutectic structure consists of B2 (NiAl) and BCC (high entropy phase) lamellae. Yield strength gradually increases from hypo-EHEA to EHEA, and then to hyper-EHEA. Yield strength and microhardness have an increase trend: I-8.7< II-14.5< III-10.0 EHEA.